Eliseo Verón. Mediatization of politics: trajectories - Fausto Neto, Antonio (2019)
This work deals with Eliseo Verón’s work and has the purpose of configuring some key moments of his investigations, published in different languages, about the mediatization process of politics. The clipping is organized as a kind of guiding enunciation and allows us to observe a mapping of concepts and ideas elaborated by Verón throughout his extensive academic and intellectual trajectory on the articulation between mediatization, political enunciation, television, discursive strategies, the Internet, new collective actors.